Physical and emotional perception in the physical education classroom among university students of Early Childhood Education - Silva Piñeiro, Roberto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Emotional and physical education are basic elements of our health that are not sufficiently introduced in the university training of future Early Childhood Education teachers. There is evidence of the benefits of physical practice on emotional health and academic performance. A socio-motor intervention of 11 practical sessions was carried out with a group of 64 students of the Early Childhood Education Degree. The emotional intelligence data with TMMS-24 were adequate, except for the reparation factor in males. The perception of fatigue remained at moderate levels and improved throughout the intervention. A weak direct correlation between final fatigue and emotional intelligence was observed. Considering the worsening of emotional and physical health levels among children and young people, it will be necessary to raise awareness and expertise on emotional and physical health among university students in the field of education, and to implement more studies and programmes in the rest of the educational stages.